Hepatocellular carcinoma: measures to improve the outlook in sub-Saharan Africa. (November 2022) - Spearman, C Wendy; Dusheiko, Geoffrey; Jonas, Eduard; Abdo, Abdelmounem; Afihene, Mary; Cunha, Lina; Desalegn, Hailemichael; Kassianides, Chris; Katsidzira, Leolin; Kramvis, Anna; Lam, Philip; Lesi, Olufunmilayo A; et al.
Summary: Hepatocellular carcinoma is a leading public health concern in sub-Saharan Africa, and it is most prevalent in young adults (median 45 years [IQR 35–57]). Overall, outcomes are poor, with a median survival of 2·5 months after presentation. Major risk factors for hepatocellular carcinoma are hepatitis B virus (HBV), hepatitis C virus, aflatoxin B1 exposure, and alcohol consumption, with metabolic dysfunction-associated fatty liver disease slowly emerging as a risk factor over the past few years. Crucially, these risk factors are preventable and manageable with effective implementation of the HBV birth-dose vaccination, treatment of chronic viral hepatitis, provision of harm reduction services, and by decreasing aflatoxin B1 exposure and harmful alcohol consumption. Primary prevention is central to the management of hepatocellular carcinoma, especially in poorly resourced environments. Effective screening and surveillance programmes with recall policies need to be implemented, because detection and curative management of hepatocellular carcinoma is possible if it is detected at an early stage, even in countries with minimal resources, with appropriate upskilling of medical personnel. The establishment of centres of excellence with advanced diagnostic and therapeutic capabilities within countries should improve hepatocellular carcinoma outcomes and assist in driving the implementation of much needed systematic data systems focused on hepatocellular carcinoma to establish the accurate burden in sub-Saharan Africa. Such data would support the public health importance of hepatocellular carcinoma and provide a strong basis for advocacy, programme development, resource allocation, and monitoring of progress in reducing mortality.